Access to antiepileptic drug therapy in children in Camagüey Province, Cuba - Bárzaga Arencibia, Zeina; López Leyvac, Alberto; Mejías Peñad, Yordanka; González Reyes, Alba Rosa; Acosta Nápolez, Maurilys; Carbonell Perdomo, Demetrio; Fernández Manzano, Edita; Choonara, Imti (Wiley, 2012)
bjective  To describe access to antiepileptic drug therapy and estimate the prevalence of epilepsy in children in Camagüey Province, Cuba.